Finite Element and Experimental Analysis of the Torsional Stiffness of a Chassis of a Baja SAE Prototype - Motta Barbosa, Luís Felipe Ferreira [UNESP]; Tomazini, José Elias [UNESP]; Martins, Marcelo Sampaio [UNESP]; Querido Moreira, Lucas Reis Rangel [UNESP]; Tokuue Hori, Marcos Yukio [UNESP]; Silva, Luís Felipe Santos (SAE International, 2016)
The torsional stiffness of a chassis is one of the most important properties of a vehicle's structure, once a low torsional stiffness has many negative effects, especially in handling characteristics. For the first time, the torsional stiffness was considered on the design of a Baja SAE prototype of the team from UNESP - FEG, Equipe Piratas do Vale. In this work, a finite element analysis is first performed in order to evaluate the torsional stiffness of this prototype, called MB1114. Then, an experimental evaluation of this parameter is executed, detailing the post-processing of the results, such as the hysteresis effect and uncertainty analysis. It also shows that it is possible to measure the torsional stiffness of chassis with a low experimental uncertainty without spending too much. The test rig used is simple to be produced and can be easily stocked. Those features are important for Baja and Formula SAE teams. After performing the finite element analysis, a result 13.4% higher than the measured value was reached. This difference is believed to be due to the finite element model inaccuracy, in other words, it came from the fact that is not possible to simulate every detail present on the real model.